Kabeljau-Stellnetzfischerei vor der ostfriesischen Küste im Herbst/Winter 1984/85 - Mentjes, Tönjes (1985)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010